Polymer mixed conductor and preparation method and application thereof

By introducing the sulfone-based small molecule conductors into the conductive polymer, a polymer hybrid conductor with both ion and electron transport capabilities was prepared, which solved the problems of low ionic conductivity and electrochemical stability of the positive electrode of the solid-state battery, and achieved higher cyclic stability and Coulomb efficiency.

CN119905289APending Publication Date: 2025-04-29SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311405303.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The mixed ion-electron conductors of the positive electrode of existing solid-state batteries have low ion conductors at room temperature, and the presence of conductive carbon will catalyze the oxidation and decomposition of the electrolyte, resulting in poor electrochemical stability.

Method used

The solid sulfone-based small molecule conduction components are introduced into the conductive polymer, and a polymer hybrid conductor with both ion and electron transport capabilities is prepared, and applied to the positive electrode of the solid-state battery.

Benefits of technology

It improves the electrochemical performance of the positive electrode of the solid-state battery, reduces the porosity, increases the proportion of active substance mass, and improves the cycle stability and Coulomb efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905289A_ABST
    Figure CN119905289A_ABST
Patent Text Reader

Abstract

The invention provides a polymer mixed type conductor and a preparation method and application thereof. The polymer mixed conductor comprises a conductive polymer, a sulfone micromolecule additive and an electrolyte salt; the mass ratio of the sulfone micromolecule additive to the electrolyte salt is (1-3): (1-3). According to the invention, a solid sulfone micromolecular conductive ion component combined with an electrolyte salt is introduced into a conductive polymer to obtain a polymer mixed conductor with ion and electron transport capabilities, and the polymer mixed conductor is applied to a positive electrode of a solid-state battery, so that the electrochemical performance of the solid-state battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conductor materials, and in particular relates to a polymer mixed conductor and a preparation method and application thereof. Background Art

[0002] As one of the most promising energy storage devices, solid-state batteries have the advantages of high energy density and high safety performance. The positive electrode materials of solid-state batteries usually include four parts: positive electrode active material particles, carbon conductive agents that enhance electronic conductivity, polymer binders, and solid electrolytes that enhance ionic conductivity. Researchers use the optimization of solid-state battery components (positive electrode, negative electrode, binder or solid electrolyte) and the interface structure between their components to improve the storage capacity and long-term stability of solid-state batteries. Although the positive electrode active material dominates the theoretical capacity and does affect the overall battery performance to a large extent, the multiple interfaces inside the battery and the resistive properties of most polymer binders have been shown to limit the further development of the battery's electrical performance.

[0003] Mixed ion-electron conductors (MIECs for short) are a class of organic polymers that can conduct both ions and electrons, which can reduce the overall resistance of solid-state battery cathode composites and provide structural integrity of traditional adhesives. Researchers introduced ion-conductive side chains on the electron-conductive skeleton and explored the balance between ion and electron conduction. However, the room temperature ionic conductivity of mixed ion-electron conductors used in solid-state battery cathodes disclosed in the prior art is generally not high, and the presence of conductive carbon in the solid-state battery cathode catalyzes the oxidative decomposition of the electrolyte, resulting in poor electrochemical stability of the battery. In addition, the currently disclosed synthesis methods of mixed ion-electron conductors are cumbersome and complex, and the cost is too high.

[0004] Therefore, it is necessary to further design and prepare an organic mixed conductor material that has both ionic conductivity, electronic conductivity and adhesion, so as to reduce the interface resistance of the electrode while maintaining the electrochemical stability of the battery, thereby improving the battery's rate performance and cycle stability. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a polymer hybrid conductor and its preparation method and application. The present invention introduces a solid sulfone small molecule ion-conducting component into a conductive polymer to obtain a polymer hybrid conductor with both ion and electron transport capabilities, and applies it to the positive electrode of a solid-state battery, thereby improving the electrochemical performance of the solid-state battery.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a polymer hybrid conductor, wherein the polymer hybrid conductor comprises a conductive polymer, a sulfone small molecule additive and an electrolyte salt;

[0008] The mass ratio of the sulfone small molecule additive to the electrolyte salt is (1-3):(1-3).

[0009] The present invention aims to solve the technical problems that the room temperature ionic conductivity of the organic mixed conductors of the solid-state battery positive electrode disclosed in the prior art is generally low, and the presence of conductive carbon in the solid-state battery positive electrode catalyzes the oxidative decomposition of the electrolyte, resulting in poor electrochemical stability of the battery. A solid sulfone small molecule ion-conducting component is introduced into a conductive polymer to obtain a polymer mixed conductor with both ion and electron transport capabilities, and the conductor is applied to the solid-state battery positive electrode. The prepared solid-state battery positive electrode has a lower porosity and a higher active material mass ratio. At the same time, the assembled solid-state battery has excellent cycle stability and high coulombic efficiency.

[0010] In the present invention, the mass ratio of the sulfone small molecule additive to the electrolyte salt is (1-3):(1-3), for example, it can be 1:1, 1:2, 1:3, 2:1, 3:1, 2:3, 3:2, etc.

[0011] In the present invention, the mass ratio of the sulfone small molecule additive and the electrolyte salt is adjusted so that ions can be efficiently transmitted. A too low or too high mass ratio is not conducive to ion transmission.

[0012] Preferably, the mass ratio of the sulfone small molecule additive to the electrolyte salt is 2:1.

[0013] In the present invention, by further adjusting the mass ratio of the sulfone small molecule additive and the electrolyte salt, it can exert a better ion transport effect in the mixed conductor.

[0014] Preferably, the sulfone small molecule additive includes any one of 3-cyclobutene sulfone, 3-cyclobutene sulfone-3-methyl carboxylate, bis(4-fluorophenyl)sulfone or phenyl vinyl sulfone, or a combination of at least two thereof.

[0015] In the present invention, by selecting the above-mentioned type of sulfone small molecule additive, it has the advantages of high ion conductivity, high interface stability and low cost.

[0016] Preferably, the conductive polymer includes any one of PEDOT:PSS, polypyrrole, polythiophene, polyaniline or polyacetylene, or a combination of at least two thereof.

[0017] Preferably, the electrolyte salt includes a lithium salt or a sodium salt.

[0018] Preferably, the lithium salt includes any one of LiTFSI, LiPF6, LiFSI, LiClO4, LiBF4, LiDFOB or LiBOB, or a combination of at least two thereof.

[0019] Preferably, the sodium salt comprises any one of NaTFSI, NaPF6 or NaFSI, or a combination of at least two thereof.

[0020] In a second aspect, the present invention provides a method for preparing the polymer hybrid conductor according to the first aspect, the method comprising the following steps:

[0021] The sulfone small molecule additive and the electrolyte salt are mixed once to obtain a precursor material; the conductive polymer solution and the precursor material are mixed twice, and the polymer mixed conductor is obtained after drying.

[0022] Preferably, the mass ratio of the sulfone small molecule additive to the electrolyte salt is (1-3):(1-3), preferably 2:1, for example, it can be 1:1, 1:2, 1:3, 2:1, 3:1, 2:3, 3:2, etc.

[0023] Preferably, the temperature of the first mixing is 50° C. and the time is 1 hour.

[0024] Preferably, the primary mixing is performed under an inert atmosphere.

[0025] Preferably, the conductive polymer solution comprises a conductive polymer and a solvent.

[0026] Preferably, the solvent comprises dimethyl sulfoxide.

[0027] Preferably, the mass concentration of the conductive polymer solution is 0.5%-5%, for example, it can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5% and the like.

[0028] Preferably, the mass ratio of the precursor material to the conductive polymer is (1-3):(1-3), preferably 1:1, for example, it can be 1:1, 1:2, 1:3, 2:1, 3:1, 2:3, 3:2, etc.

[0029] In the present invention, the mass ratio of the precursor material and the conductive polymer is adjusted to maximize the electron transmission and ion transmission capabilities. If the mass ratio is too low, the electron transmission will be limited, and vice versa, the ion transmission will be limited.

[0030] Preferably, the secondary mixing is performed under an inert atmosphere.

[0031] In a third aspect, the present invention provides a positive electrode sheet, comprising a current collector and a positive electrode active material layer disposed on one side of the current collector, wherein the positive electrode active material layer comprises the polymer hybrid conductor according to the first aspect.

[0032] In a fourth aspect, the present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet is the positive electrode sheet according to the third aspect.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The present invention provides a polymer hybrid conductor, which aims to solve the technical problems that the room temperature ionic conductivity of the organic hybrid conductor of the solid-state battery positive electrode disclosed in the prior art is generally low, and the presence of conductive carbon in the solid-state battery positive electrode will catalyze the oxidative decomposition of the electrolyte, resulting in poor electrochemical stability of the battery. A solid sulfone small molecule ion-conducting component is introduced into a conductive polymer to obtain a polymer hybrid conductor with both ion and electron transport capabilities, and the conductor is applied to the solid-state battery positive electrode. The prepared solid-state battery positive electrode has a lower porosity and a higher mass percentage of active substances. At the same time, the assembled solid-state battery has excellent cycle stability and high coulombic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 A schematic diagram of the structure of a polymer hybrid conductor provided in Example 1;

[0036] Figure 2 Scanning morphology images of the positive electrode sheet prepared from the polymer mixed conductor provided in Example 1 at different magnifications;

[0037] Figure 3 Performance diagram of lithium-ion battery provided for Application Example 1 after 100 cycles at 30°C;

[0038] Figure 4 Coulombic efficiency diagram of the lithium-ion battery provided for Application Example 1 after 100 cycles at 30°C. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is further described below by combining the accompanying drawings and specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0040] Example 1

[0041] This embodiment provides a polymer hybrid conductor, which includes PEDOT:PSS, 3-cyclobutene sulfone and LiTFSI; the mass ratio of PEDOT:PSS, 3-cyclobutene sulfone and LiTFSI in the polymer hybrid conductor is 3:2:1.

[0042] This embodiment also provides a method for preparing the above polymer mixed conductive paste, which comprises the following steps:

[0043] In a glove box, 3-cyclobutene sulfone and LiTFSI were heated at 50°C and stirred for 1 hour to obtain a precursor material; after the PEDOT:PSS particles were dried in an oven, the dried PEDOT:PSS particles were dissolved in a dimethyl sulfoxide solvent, ultrasonicated for 15 minutes and magnetically stirred for 24 hours to obtain a PEDOT:PSS solution with a mass concentration of 2wt%, and then the PEDOT:PSS solution and the precursor material were stirred in a drying room for 3 hours, wherein the mass ratio of the precursor material to the conductive polymer was 1:1, to obtain a polymer mixed conductor slurry.

[0044] This embodiment provides a positive electrode sheet, and the preparation method of the positive electrode sheet is as follows:

[0045] Taking the total mass of the polymer mixed conductor slurry as 100%, 90% by mass of lithium iron phosphate and the polymer mixed conductor slurry are stirred for 8 hours until uniform, coated on aluminum foil, vacuum dried and rolled to obtain a positive electrode sheet coated with a polymer mixed conductor, such as Figure 1-2 shown.

[0046] Example 2

[0047] This embodiment provides a polymer hybrid conductor, which includes PEDOT:PSS, 3-cyclobutene sulfone and LiTFSI; the mass ratio of PEDOT:PSS, 3-cyclobutene sulfone and LiTFSI in the polymer hybrid conductor is 6:2:1.

[0048] This embodiment also provides a method for preparing the above-mentioned polymer mixed conductor, which comprises the following steps:

[0049] In a glove box, 3-cyclobutene sulfone and LiTFSI were heated at 50°C and stirred for 1 hour to obtain a precursor material; after the PEDOT:PSS particles were dried in an oven, the dried PEDOT:PSS particles were dissolved in a dimethyl sulfoxide solvent, ultrasonicated for 15 minutes and magnetically stirred for 24 hours to obtain a PEDOT:PSS solution with a mass concentration of 2wt%, and then the PEDOT:PSS solution and the precursor material were stirred in a drying room for 3 hours, wherein the mass ratio of the precursor material to the conductive polymer was 1:2, to obtain a polymer mixed conductor slurry.

[0050] This embodiment provides a positive electrode sheet, and the preparation method of the positive electrode sheet is as follows:

[0051] Taking the total mass of the polymer mixed conductor slurry as 100%, 90% of lithium cobalt oxide and the polymer mixed conductor slurry are stirred for 8 hours until uniform, coated on aluminum foil, vacuum dried and rolled to obtain a positive electrode sheet coated with a polymer mixed conductor.

[0052] Example 3

[0053] This embodiment provides a polymer hybrid conductor, which includes PEDOT:PSS, 3-cyclobutene sulfone and LiTFSI; the mass ratio of PEDOT:PSS, 3-cyclobutene sulfone and LiTFSI in the polymer hybrid conductor is 3:4:2.

[0054] This embodiment also provides a method for preparing the above-mentioned polymer mixed conductor, which comprises the following steps:

[0055] In a glove box, 3-cyclobutene sulfone and LiTFSI were heated at 50°C and stirred for 1 hour to obtain a precursor material; after the PEDOT:PSS particles were dried in an oven, the dried PEDOT:PSS particles were dissolved in a dimethyl sulfoxide solvent, ultrasonicated for 15 minutes and magnetically stirred for 24 hours to obtain a PEDOT:PSS solution with a mass concentration of 2wt%, and then the PEDOT:PSS solution and the precursor material were stirred in a drying room for 3 hours, wherein the mass ratio of the precursor material to the conductive polymer was 2:1, to obtain a polymer mixed conductor slurry.

[0056] This embodiment provides a positive electrode sheet, and the preparation method of the positive electrode sheet is as follows:

[0057] Taking the total mass of the polymer mixed conductor slurry as 100%, 90% by mass of lithium iron phosphate and the polymer mixed conductor slurry are stirred for 8 hours until uniform, coated on aluminum foil, vacuum dried and rolled to obtain a positive electrode sheet coated with a polymer mixed conductor.

[0058] Example 4

[0059] The difference between this embodiment and embodiment 1 is that the mass ratio of PEDOT:PSS, 3-cyclobutene sulfone and LiTFSI in the polymer mixed conductor is 9:2:1, and the rest is the same as embodiment 1.

[0060] Example 5

[0061] The difference between this embodiment and embodiment 1 is that the mass ratio of PEDOT:PSS, 3-cyclobutene sulfone and LiTFSI in the polymer mixed conductor is 1:2:1, and the rest is the same as embodiment 1.

[0062] Example 6

[0063] The difference between this embodiment and embodiment 1 is that 3-cyclobutene sulfone is replaced by 3-cyclobutene sulfone-3-methyl carboxylate of the same content, and the rest is the same as embodiment 1.

[0064] Example 7

[0065] The difference between this embodiment and embodiment 1 is that the mass ratio of 3-cyclobutene sulfone to LiTFSI in the polymer mixed conductor is 1:4, and the rest is the same as embodiment 1.

[0066] Example 8

[0067] The difference between this embodiment and embodiment 1 is that the mass ratio of 3-cyclobutene sulfone to LiTFSI in the polymer mixed conductor is 4:1, and the rest is the same as embodiment 1.

[0068] Example 9

[0069] The difference between this embodiment and embodiment 1 is that the mass ratio of PEDOT:PSS to the precursor material is 4:1, and the rest is the same as embodiment 1.

[0070] Example 10

[0071] The difference between this embodiment and embodiment 1 is that the mass ratio of PEDOT:PSS to the precursor material is 1:4, and the rest is the same as embodiment 1.

[0072] Comparative Example 1

[0073] The difference between this comparative example and Example 1 is that 3-cyclobutene sulfone is replaced by LiTFSI of the same content, and the rest is the same as Example 1.

[0074] Comparative Example 2

[0075] The difference between this comparative example and Example 1 is that 3-cyclobutene sulfone is replaced by polyethylene oxide (PEO) of the same content, and the rest is the same as Example 1.

[0076] Test conditions

[0077] The mixed conductor type lithium iron phosphate positive electrodes provided in Examples 1 to 10 and Comparative Examples 1 to 2 were assembled into lithium ion batteries, and the lithium ion batteries were tested. The test method is as follows:

[0078] After 2 cycles at 0.1C and then a long cycle at 0.5 / 1C, the charge and discharge cut-off voltage was 2.5-3.9V.

[0079] The test results are shown in Table 1:

[0080] Table 1

[0081]

[0082]

[0083] It can be seen from Table 1 that Figure 3-4 As shown, the battery provided by Application Example 1 has the best cycle performance, with a capacity retention rate of 101.4% and an average coulombic efficiency of 100.1% after 100 cycles. The batteries provided by Application Examples 2-6 have a capacity retention rate of more than 90% after 100 cycles, but the cycle stability and coulombic efficiency are lower than those of Application Example 1. The batteries in Application Examples 7-10 and Comparative Application Examples 1-2 have a problem of transmission obstruction during the battery cycle because a continuous and effective ion or electron transmission path is not constructed inside the positive electrode, and the capacity retention rate is reduced to 0% after 100 cycles.

[0084] The present invention selects the mass ratio of the sulfone small molecule additive, the electrolyte salt and the conductive polymer within a preferred range, so that the battery can obtain a higher capacity retention rate and coulombic efficiency. Among them, the cycle performance of application example 1 is the best, so it is the preferred ratio scheme.

[0085] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A polymer hybrid conductor, characterized in that: The polymer mixed conductor comprises a conductive polymer, a sulfone small molecule additive and an electrolyte salt; The mass ratio of the sulfone small molecule additive to the electrolyte salt is (1-3):(1-3).

2. The polymer hybrid conductor according to claim 1, characterized in that: The mass ratio of the sulfone small molecule additive to the electrolyte salt is 2:1; Preferably, the mass ratio of the sulfone small molecule additive and the electrolyte salt to the conductive polymer is (1-3):(1-3), preferably 1:

1.

3. The polymer hybrid conductor according to claim 1 or 2, characterized in that: The sulfone small molecule additive includes any one of 3-cyclobutene sulfone, 3-cyclobutene sulfone-3-methyl carboxylate, bis(4-fluorophenyl)sulfone or phenyl vinyl sulfone, or a combination of at least two thereof.

4. The polymer hybrid conductor according to any one of claims 1 to 3, characterized in that: The conductive polymer includes any one of PEDOT:PSS, polypyrrole, polythiophene, polyaniline or polyacetylene, or a combination of at least two thereof.

5. The polymer hybrid conductor according to any one of claims 1 to 4, characterized in that: The electrolyte salt includes a lithium salt or a sodium salt; Preferably, the lithium salt comprises any one or a combination of at least two of LiTFSI, LiPF6, LiFSI, LiClO4, LiBF4, LiDFOB or LiBOB; Preferably, the sodium salt comprises any one of NaTFSI, NaPF6 or NaFSI, or a combination of at least two thereof.

6. A method for preparing a polymer hybrid conductor according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: The sulfone small molecule additive and the electrolyte salt are mixed once to obtain a precursor material; the conductive polymer solution and the precursor material are mixed twice, and the polymer mixed conductor is obtained after drying.

7. The method according to claim 6, characterized in that The mass ratio of the sulfone small molecule additive to the electrolyte salt is (1-3):(1-3), preferably 2:1; Preferably, the temperature of the first mixing is 50°C and the time is 1 hour; Preferably, the primary mixing is performed under an inert atmosphere.

8. The method according to claim 6 or 7, characterized in that: The conductive polymer solution comprises a conductive polymer and a solvent; Preferably, the solvent comprises dimethyl sulfoxide; Preferably, the mass concentration of the conductive polymer solution is in the range of 0.5%-5%; Preferably, the mass ratio of the precursor material to the conductive polymer is (1-3):(1-3), preferably 1:1; Preferably, the secondary mixing is performed under an inert atmosphere.

9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a current collector and a positive electrode active material layer disposed on one side of the current collector, wherein the positive electrode active material layer comprises the polymer mixed conductor according to any one of claims 1 to 5.

10. A secondary battery, characterized in that: The secondary battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, and the positive electrode sheet is the positive electrode sheet according to claim 9.